2018
DOI: 10.1021/acssuschemeng.7b04489
|View full text |Cite
|
Sign up to set email alerts
|

The High Performance of Choline Arginate for Biomass Pretreatment Is Due to Remarkably Strong Hydrogen Bonding by the Anion

Abstract: The ionic liquid choline arginate [Ch][Arg] is more effective for biomass pretreatment than other choline based amino acid ILs, but the underlying mechanism has been unclear. In the present work we use the highlevel CCSD(T)/CBS(MP2) and G4(MP2) thermochemical protocols to probe the H-bonding interactions of [Ch][Arg] with water, and organic functional groups commonly found in biomass. We show that the [Ch][Arg] IL forms unusually strong H-bonding interactions with prototypical H-bond donors. For example, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…The strength of the H-bonds varied considerably with the donor group, but H-bonds with [Arg] were always considerably stronger than those with [Gly]. 26 These high-level calculations could only be performed on small model systems composed of one cation, one anion, and a simple hydrogen bond donor. Thus, it is open to question whether a cation charge group is located in position to polarize hydrogen bonds with the guanidine nitrogen in the bulk bio-IL.…”
Section: Cholinium Amino Acid Ils ([Ch]mentioning
confidence: 99%
See 3 more Smart Citations
“…The strength of the H-bonds varied considerably with the donor group, but H-bonds with [Arg] were always considerably stronger than those with [Gly]. 26 These high-level calculations could only be performed on small model systems composed of one cation, one anion, and a simple hydrogen bond donor. Thus, it is open to question whether a cation charge group is located in position to polarize hydrogen bonds with the guanidine nitrogen in the bulk bio-IL.…”
Section: Cholinium Amino Acid Ils ([Ch]mentioning
confidence: 99%
“…Our previous ab initio calculations revealed that strong hydrogen bonds between the guanidine group and model HBDs were due to bond polarization by the nearby choline charge center. 26 Figure 5A shows that 2.3 ± 1.2 (1:3 [Ch][Arg]/water) and 1.3 ± 1.0 (1:10 [Ch][Arg]/water) cation charge centers are closely correlated with the guanidine group (cyan data) at average separations of 5.1 and 5.8 Å, respectively. While 0.5−1.2 Å larger than the ab initio calculated distances, these data show that correlations between the guanidine group and cation charge center do persist in the bulk liquid.…”
Section: T H Imentioning
confidence: 99%
See 2 more Smart Citations
“…[54] Some correlation with e.g. anion basicity, charge density, or local structure have been identified, [55] but a fuller understanding awaits systematic studies that correlate performance with structural variation. The diversity of naturally-occurring (and synthetic amino acid) structures includes potentially amphiphilically nanostructured ILs and their solutions, but how this may correlate to process efficiency remains an open question.…”
Section: Introductionmentioning
confidence: 99%